2019
DOI: 10.1111/jsr.12869
|View full text |Cite
|
Sign up to set email alerts
|

Associations between sleep disturbances, mental health outcomes and burnout in firefighters, and the mediating role of sleep during overnight work: A cross‐sectional study

Abstract: This study investigated whether sleep disorder risk and mental health outcomes in firefighters were associated with burnout, particularly emotional exhaustion, and examined the mediating role of sleep at work in these relationships. A secondary aim was to investigate associations between habitual sleep characteristics and burnout. North American firefighters (n = 6,307) completed the Maslach Burnout Inventory (emotional exhaustion, depersonalisation, personal accomplishment), and were screened for sleep disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
58
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 42 publications
3
58
1
4
Order By: Relevance
“…Typical adverse health effects of regular and heavy marijuana use are psychiatric problems, such as depression, anxiety, suicidality, psychosis [1], and schizophrenia [12][13][14]. Marijuana use has numerous consequences, including impaired respiratory function and cardiovascular disease [6], increase in myocardial infarction, and stroke prevalence [15], along with neural connectivity impairment, and hippocampus activity reduction [15]. To illustrate further, Hasin et al [5] listed the following somatic, cognitive, behavioral, and emotional consequences: cognitive decline, psychosocial impairments, higher rates of traffic accidents, emergency department visits, poor quality of life, use of other drugs [16][17][18], cannabis withdrawal syndrome, and risk of addiction.…”
Section: Introductionmentioning
confidence: 99%
“…Typical adverse health effects of regular and heavy marijuana use are psychiatric problems, such as depression, anxiety, suicidality, psychosis [1], and schizophrenia [12][13][14]. Marijuana use has numerous consequences, including impaired respiratory function and cardiovascular disease [6], increase in myocardial infarction, and stroke prevalence [15], along with neural connectivity impairment, and hippocampus activity reduction [15]. To illustrate further, Hasin et al [5] listed the following somatic, cognitive, behavioral, and emotional consequences: cognitive decline, psychosocial impairments, higher rates of traffic accidents, emergency department visits, poor quality of life, use of other drugs [16][17][18], cannabis withdrawal syndrome, and risk of addiction.…”
Section: Introductionmentioning
confidence: 99%
“…These front-line personnel suffer from high rates of poor sleep, workplace fatigue, occupational stress, burnout, emotional exhaustion, and violence in the workplace. [1][2][3][4][5] In most communities, public safety personnel maintain readiness 24 hours a day, 365 days a year. Maintaining readiness requires that many work long duration shifts, work more than 40 hours per week, and unplanned overtime hours.…”
Section: Introductionmentioning
confidence: 99%
“…The shift work nature of public safety occupations contributes to many reporting inadequate sleep, poor sleep quality, fatigue, occupational stress, emotional exhaustion, and burnout. [1][2][3][4] Previous research has shown that greater than half of police officers, firefighters, and EMS shift workers report poor sleep quality or inadequate sleep. 4,6,7 The hazards of poor sleep and workplace fatigue are numerous.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wolkow et al () conducted a cross‐sectional study on the associations between sleep disturbances, mental health and burnout in firefighters, paying special respect to the mediating role of sleep during overnight work. This study was performed in North American firefighters ( n = 6,307) who completed several questionnaires about burnout and mental health, but who were also screened for sleep disorders and self‐reported sleep characteristics.…”
mentioning
confidence: 99%